Optimisation of extraction, clarification and pasteurisation of clarified guava [psidium guajaval., cv kampuchea (gu8)] juice drink / Noor Faezah Abdullah - Abdullah, Noor Faezah (2006)
A diet of guava juice drink not only improves our health but also promotes growth and vigour to our body. Extractions of juice through the use of enzymes are more effective and cheaper becau se a small quantity of enzymes will help to extract a large amount of juice . Centrifugation of juice is a process to separate pulp from the juice in order to produc e clarifi ed juic e. Pasteurisation is important to inhibit the pectinesterase enzyme which will stabilise the cloudiness of juice and. at the same time kill to non-patho genic microor ganisms. Studi es were conducted to determine the effect of different maturity stages of guava skin colour , pulp cont ent , calcium, ascorbic acid , absorbanc e on the yield of extraction . Guava fruit at 90% maturation were selected for the preparation of clarified guava juice drink due to their high level of calcium content , absorb ance value or cloud content and guava juice yield. A pH (X i; 3.2 - 4.0), concentration of enzyme Pectinex Ultra SPL (X2; 500 - 900 ppm), temperature (X3; 30 - 50°C) and reaction time (X4; 0 - 120 min) were the four parameters manipul ated to produce a high yield extraction of guava (Kamp uchea cv Vietnamese) juice drink , which was carried out using a Response Surface Methodology (RSM). It was found that optimum yield extraction of the guava juice was obtained at the following optimum condition: pH of 3.2, enzyme concentration of 500 ppm, temperature at 50°C and reaction time of 120 minute s. Relative centrifugal field (RCF) (Xc; 600 - 1000 x g) and centrifugation time (X6; 30 70 minutes) were the two parameters adopted to produce clarified guava juice drink , which was carried out using a RSM. Optimum clarification of the guava juice drink was